Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Telkom Witel Bekasi - Silvia Jamhari; Zahra (PT. Penerbit Tiga Mutiara, 2024)
This research aims to analyze the influence of the work environment and work discipline on employee performance at PT. Telkom Witel Bekasi. Human Resources (HR) are a critical element in achieving a company's vision and mission, where employee performance is greatly influenced by environmental factors and work discipline. This study uses a quantitative approach with a population of 46 organic employees, sampled through the saturated sampling method. Data was collected through observation and questionnaires, then analyzed using data quality tests, classical assumption tests, hypothesis tests, and multiple linear regression. The results show that both the work environment and work discipline have a significant effect on employee performance, both partially and simultaneously. The work environment has a positive influence on performance by 35%, while work discipline contributes 44.2%. Simultaneously, these two variables affect employee performance by 45.7%, while the remaining 54.3% is influenced by other factors not examined. In conclusion, improving a conducive work environment and good work discipline can enhance employee performance at PT. Telkom Witel Bekasi.